A Late Complication Occurring Due to Tacrolimus After Liver Transplant: Posterior Reversible Encephalopathy Syndrome - Usta, Sertac; Karabulut, Koray (Baskent Univ, 2025)
Posterior reversible encephalopathy syndrome is a rare condition of the central nervous system that may occur in adults as well as in children. Clinically, it presents with mental status changes, visual loss, headaches, seizures, or coma. The diagnosis of posterior reversible encephalopathy syndrome is based on the typical appearance in occipital and parietal lobes in radiologic imaging studies, such as computed tomography or magnetic resonance imaging of the brain, which exhibit the typical appearance due to vasogenic edema. Causative factors include hyper-tensive encephalopathy, renal failure, preeclampsia, autoimmune conditions, and the use of cytotoxic or immunosuppressive agents. Rare cases of posterior reversible encephalopathy syndrome due to treatment with tacrolimus, an immunosuppressive agent com-monly used after organ transplant, have been reported. In these patients, the tacrolimus dose is reduced or discontinued. In transplant patients with neurologic symptoms, the possibility of posterior reversible encephalopathy syndrome should be kept in mind.
Keywords: Calcineurin inhibitor; Central nervous system; Immunosuppressive treatment; Neurologic complications